Penerapan Model Co-Op Co-Op Untuk Meningkatkan Hasil Belajar pada Mata Pelajaran PPKn - Lurdis Lopes; Septian Aji Permana (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
This study aims to improve the learning outcomes of eighth-grade students in Civic Education (PPKn) at SMP PGRI Kasihan through the implementation of the Co-op Co-op learning model. This Classroom Action Research was conducted at SMP PGRI Kasihan, Bantul, Yogyakarta, from October to November 2025, involving 27 students of class VIII B. The Minimum Mastery Criterion (KKM) was set at 75. Data were collected through observation, evaluation tests, interviews, and documentation, and were analyzed quantitatively across two learning cycles. The findings show a significant improvement in student achievement. In the pre-cycle stage, only 3 students met the KKM (41.00% mastery). This increased to 9 students (67.00% mastery) in Cycle I, and further to 24 students (77.00% mastery) in Cycle II, surpassing the 75% success indicator. The study concludes that the Co-op Co-op learning model is effective in enhancing PPKn learning outcomes by making the learning process more engaging, increasing student participation and collaboration, and facilitating better understanding of the material.